A Study on 4 Stroke Diesel Engine Noise Using Different Blends of Pongamia Oil - Kakkar, Chirag (My University, 2010)
Sound may be described as the disturbance that propagates through a physical (elastic) medium. Rather noise can be conveniently and concisely defined as unwanted sound. With the rise in population which has lead to increase in traffic and industries one of the developing problems is of “Noise”. Internal combustion engines are designed to operate on gasoline or diesel fuels (or their substitutes) have different combustion systems that lead to significantly different noise characteristics. Gasoline engines use spark ignition to control combustion process, while diesel cycle engines use compression ignition. The forces generated inside internal combustion engines cause vibration of engine structure, leading to radiated noise. With ever increasing consumption of fossil fuels and petroleum products, It is a matter of concern for our country for huge out-go of foreign exchange on the one hand and increasing emission causing environmental hazards on the other. Public at large are raising their concerns over the declining state of environment and health. With domestic crude oil output stagnating, the momentum of growth experienced a quantum jump since 1990s when the economic reforms were introduced paving the way for a much higher rate of development leading the demand for oil to continue to rise at an ever increasing pace. The situation offers us a challenge as well as an opportunity to look for substitutes of fossil fuels for both economic and environmental benefits to the country. Pongamia oil is one such substitute that can be produced from seeds of karanj and used in blends with diesel for automobiles and used for transportation of vehicles, in generators, and irrigation pumps, etc. As it is well known that with crude oil depleting every day due to its ever increasing demands future belongs to alternative fuels. Using biodiesel blends a lot of work has been done by various researchers regarding the study of engine characteristics like brake horse power, thermal efficiency, etc. but noise has been one area that requires immediate attention where still a lot of work has to be done. In the present work of engine noise using pure diesel, B10 (10% biodiesel and 90% diesel), B20 (20% biodiesel and 80% diesel) and B30 (30% biodiesel and 70% diesel) blends of biofuels has been done on points A, B, C, D (at a distance of 1 meter surrounding the engine)and at the exhaust point. It has been figured out that using B20 or B10 fuels noise reduces to considerable levels near the A, B, C, D points surrounding the engine in comparison to noise generated by pure diesel. Along with that effect of blends on 1-1 octave band frequency analysis has also been studied in order to figure under which frequency range sound pressure level is high. Attempt has also been made to study the effect of blends on acoustic power. All these studies have been done by varying compression ratios and loads at the marked locations from the engine.
M.E. (CAD/CAM and Robotics)
Keywords: Diesel engine,bio diesel; pongamia oil